2022
DOI: 10.18632/aging.203880
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism in aging simultaneously altered in liver and nervous system

Abstract: In humans, aging, triggers increased plasma concentrations of triglycerides, cholesterol, low-density lipoproteins and lower capacity of high-density lipoproteins to remove cellular cholesterol. Studies in rodents showed that aging led to cholesterol accumulation in the liver and decrease in the brain with reduced cholesterol synthesis and increased levels of cholesterol 24-hydroxylase, an enzyme responsible for removing cholesterol from the brain. Liver diseases are also related to brain aging, inducing chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 102 publications
0
12
0
1
Order By: Relevance
“…Moreover, besides a systemic effect, NAFLD has been linked to reduced cognitive functions in adults (Bertolotti, 2014 ; Seo et al, 2016 ; Takahashi et al, 2017 ; Weinstein et al, 2018 , 2019 ) and in mice, HFD has been shown to impair amygdala and hippocampus-dependent memory consolidation and cause neuroinflammation during aging (Spencer et al, 2017 ). Additionally changes in cholesterol as well as TAG levels have been linked to the neuronal aging process and the etiology of various age-related diseases including Alzheimer's (AD), Parkinson's (PD) and Huntington's disease (Spitler and Davies, 2020 ; Nunes et al, 2022 ). It has been extensively demonstrated that the responsiveness of rodent AMPK to nutrient deprivation decreases during aging (Salminen and Kaarniranta, 2012 ).…”
Section: Nutrient Signalingmentioning
confidence: 99%
“…Moreover, besides a systemic effect, NAFLD has been linked to reduced cognitive functions in adults (Bertolotti, 2014 ; Seo et al, 2016 ; Takahashi et al, 2017 ; Weinstein et al, 2018 , 2019 ) and in mice, HFD has been shown to impair amygdala and hippocampus-dependent memory consolidation and cause neuroinflammation during aging (Spencer et al, 2017 ). Additionally changes in cholesterol as well as TAG levels have been linked to the neuronal aging process and the etiology of various age-related diseases including Alzheimer's (AD), Parkinson's (PD) and Huntington's disease (Spitler and Davies, 2020 ; Nunes et al, 2022 ). It has been extensively demonstrated that the responsiveness of rodent AMPK to nutrient deprivation decreases during aging (Salminen and Kaarniranta, 2012 ).…”
Section: Nutrient Signalingmentioning
confidence: 99%
“…If the gut barrier is compromised, harmful metabolites can enter the liver, leading to oxidative damage and inflammatory responses, which in turn can affect the neural feedback between the liver and the brain . Elevated cholesterol levels in the liver of older individuals can lead to metabolic disturbances, which may potentially contribute to AD …”
Section: Introductionmentioning
confidence: 99%
“…15 Elevated cholesterol levels in the liver of older individuals can lead to metabolic disturbances, which may potentially contribute to AD. 16 Probiotics are defined as "live microorganisms", capable of conferring health benefits to the host when administered in adequate amounts and can regulate gut microbiota directly. 17 impairment via the regulation of the gut−brain axis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that cholesterol levels in the central nervous system are closely related to cognitive function [ 9 , 10 ]. On one hand, the close association between cholesterol and various aspects of brain function, such as cytotropic support, neuronal activity, and neural information transmission, highlights its significance as a crucial component of neurons [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%